Evaluasi Pengelolaan Obat Di Instalasi Farmasi Rumah Sakit Umum Daerah Provinsi NTB Tahun 2017 - nur oktaviani; Gunawan Pamudji (Jurnal Farmasi Indonesia, 2018)
IFRS is responsible for drug management, namely selection, planning and procurement, distribution and use. Preliminary observations indicate of drug management problems in IFRSUD Province NTB. The aim of the study was to evaluate of drug management in IFRSUD Province NTB. Descriptive research were taken retrospectively and concurrently. Data in the form of quantitative and qualitative, accompanied by interviews of related parties. All stages of drug management measured using the MOH RI indicator, Pudjaningsih, Permenkes and WHO then compared with the results of other studies. The results showed that the stage that did not meet the standards were: the stage of selection: conformity with the national formulary; procurement: percentage of available fund allocation, namely the frequency of incomplete SP / Invoice, percentage of available capital funds with the total needed, frequency of delay in payment by the hospital against the agreed time, the percentage of suitability between drug planning and the reality of each drug; distribution, the accuracy of the amount of drug data on the automatic stock card, Turn Over Ratio, percentage and value of drugs that were damaged / expired, percentage of dead stock; usage: number of drug items per recipe, percentage of antibiotic, and percentage of prescription injection drugs. The results are in accordance with the standards, the stage of selection suitability with hospital formulary; procurement: frequency of procurement of each drug item per year; distribution: namely drug availability level; use, percentage of prescription with a generic name, percentage of drugs that can submitted, percentage of drug that label, and the average time spent serving recipes